KONTRIBUSI KELINCAHAN DAN KELENTUKAN TERHADAP KEMAMPUAN PASSING BAWAH DALAM PERMAINAN BOLA VOLI PESERTA KELAS XI MAN 2 OGAN KOMERING ILIR - Dimas Andika; Surisman; M. Fajril Rifaldo; Lungit Wicaksono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the contribution of agility and flexibility to the ability of underhand passing in volleyball among eleventh-grade students of MAN 2 Ogan Komering Ilir. The research method used was a correlational method. The research sample consisted of 50 students. The research instruments used were agility, flexibility, and underhand passing tests. The research hypotheses were: (1) there is a contribution of agility to underhand passing ability, (2) there is a contribution of flexibility to underhand passing ability, and (3) there is a contribution of agility and flexibility simultaneously to underhand passing ability. The results of the study showed that: (1) there was a significant relationship between agility and underhand passing ability (r calculated = 0.499 > r table = 0.088), (2) there was a significant relationship between flexibility and underhand passing ability (r calculated = 0.681 > r table = 0.088), and (3) simultaneously, agility and flexibility had a significant relationship with underhand passing ability (r calculated = 0.716 > r table = 0.088) with a contribution of 51.26%.